2016
DOI: 10.1177/1359105316664135
|View full text |Cite
|
Sign up to set email alerts
|

‘Do you mean I’m not whole?’: Exploring the role of support in women’s experiences of mastectomy without reconstruction

Abstract: This study explores the role of others in supporting younger women who opt not to reconstruct their breast post-mastectomy. Semi-structured interviews were conducted with six women, diagnosed with breast cancer in their 30s/40s. The women lived in England, had been diagnosed a minimum of 5 years previously and had undergone unilateral mastectomy.An interpretative phenomenological analysis revealed three themes; Assuring the self: "I'll love you whatever", Challenging the self: 'Do you mean I'm not whole?', and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Women should be encouraged to explore their physical, emotional and spiritual well-being and the role BR may play for them 89. Throughout this process, by optimising the acceptability of the option of BR, women could select in an informed manner a treatment plan which may or may not include BR that best fits their desires and needs 89 91. Ensuring that patients and providers consider BR as an acceptable part of care for women with breast cancer will likely improve access to BR; future research is needed to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Women should be encouraged to explore their physical, emotional and spiritual well-being and the role BR may play for them 89. Throughout this process, by optimising the acceptability of the option of BR, women could select in an informed manner a treatment plan which may or may not include BR that best fits their desires and needs 89 91. Ensuring that patients and providers consider BR as an acceptable part of care for women with breast cancer will likely improve access to BR; future research is needed to evaluate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be linked to sexual anxiety, specifically in relation to damaging the breasts, inflicting pain and/or concerns around causing the cancer to return during sexual intercourse (Marshall & Kiemle, ). Moreover, qualitative research suggests unconditional spousal support facilitates emotional intimacy following mastectomy without reconstruction (Archer, Holland, & Montague, ). Therefore, spousal reaction following breast reconstruction requires additional research to determine whether there is a need for sex therapy/psychosexual therapy for couples following reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, spontaneous selfaffirmation (engaging in self-affirming thoughts in response to a threat) is positively related to psychological well-being (Emanuel et al, 2018). From a survivorship perspective, there are many potential threats to integrity of self and wellbeing, from initial diagnosis through treatments and transition to life post-treatment (Allen et al, 2009;Archer et al, 2018). Research examining the self-affirming capacity of expressive writing among early-stage breast cancer survivors showed that expressive writing was associated with fewer physical symptoms at follow-up (Creswell et al, 2007).…”
Section: Values and Self-affirmationmentioning
confidence: 99%